Vision tracking application for mobile navigation using Humanoid robot Nao - Ariffin, Ilmi Mohd; Rasidi, Ahmad Ismat Hakam Mohamed; Yussof, Hanafiah; Miskam, Mohd Azfar; Omar, Abdul Rahman (2015 International Symposium on Micro-NanoMechatronics and Human Science (MHS), 2015)
This project presents a new approach of humanoid-operated mobile platform. The robot used in this work is Nao by Aldebaran Robotics. Nao is chosen because of its versatility. Its wide range of movements allows it to perform various tasks such as steering through a simple programming algorithm. Arduino microcontroller target board is used to provide the interface between Nao robot and the mobile platform. This project consist of several parts. This study will focuses on the development of mobile platform, integration of Arduino microcontroller programming with Nao's Choregraphe, navigation with obstacle avoidance and finally navigation with human following ability by implementing Nao Mark visual tracking.